KEBIJAKAN PENDIDIKAN INDONESIA: KEBIJAKAN BERBASIS RISET - Joni Herri, Sar (STKIP Subang, 2015)
Technological achievements of the 21th century has affected all aspects of social, political, cultural, Educational, and religious. In the field of education, education reform must be done in order to remain relevant to contemporary circumstances. Therefore, vigorous research activities carried out by the government, namely the Ministry of Education and Culture, education practitioners, students and professors of the universities, and teachers at the school. But unfortunately, most of the results of these studies are still struggling in the micro range. Within the framework of basic education in the Graduate School of Education University of Indonesia. Since 2006 until 2013, virtually no research has